A customized protocol to generate STR profiles from latent fingerprints. (December 2022) - Di Nunzio, Michele; Rodríguez-Lozoya, Ana María; De Alcaraz-Fossoul, Josep; Barrot-Feixat, Carme
Abstract: For decades, dactyloscopical and DNA analyses have both played a key role in forensic investigations involving friction skin patterns and/or human biological material. In many occasions, friction ridge impressions may hold little discriminatory power due to low quality of ridge patterns and/or insufficient area extension of such patterns. In these cases, an appropriate human DNA collection and a high-quality DNA extraction become crucial steps to yield a genetic identity from an unsuitable latent fingerprint pattern. Indeed, over the past few years, it has been proven that complete Short Tandem Repeat (STR) profiles can be obtained from a touch DNA sample. In this study, a protocol has been customized to maximize the performance of genetic profiling from latent fingerprints. Six participants provided two sets of finger impressions on pre-cleaned glass surfaces. These impressions were generated by the participant's dominant (DH) and non-dominant hand (NDH). Genetic material from fingerprints was pooled using a cotton swab for each donor and hand, combining 1–5 depositions consecutively. This was followed by DNA extraction, Real-Time PCR for DNA quantification, capillary electrophoresis (CE) for sequencing, and genotyping software for STR profiling. DNA yield was measured by ng/cm 2 (DNA/fingerprint area). Statistical tests detected DNA yield differences by donor's sex, age distribution, handedness and fingerprint pooling. Results revealed that DNA quantities from DH was dependent on the number of pooled fingerprints. However, NDH yielded similar DNA quantities across all fingerprint pooled combinations. With the aid of a customized protocol, DNA titers was improved and meaningful STR profiles were produced for donors' DH and NDH.